2021
DOI: 10.1111/bjc.12320
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the effects of social‐cognitive training in schizophrenia: The role of treatment characteristics and study quality

Abstract: Objectives. This meta-analysis was designed to assess the effects of social-cognitive training (SCT) and whether study quality, treatment approach, treatment context, and sample characteristics influence these effects.Methods. Electronic databases were searched up to 5 August 2020 using variants of keywords: 'social cognition', 'training', 'rehabilitation', 'remediation', and 'schizophrenia'. Methodological moderators were extracted through the Clinical Trials Assessment Measure and verified by authors. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…In a previous systematic review and meta-analysis ( Nijman et al, 2020 ), psychosocial approaches, e.g., social-cognitive training (SCT), have been shown to improve several domains of social cognition, including emotion recognition and social perception. Among them, SCT provides non-pharmacological modality that particularly improve the domain of emotion recognition ( Yeo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous systematic review and meta-analysis ( Nijman et al, 2020 ), psychosocial approaches, e.g., social-cognitive training (SCT), have been shown to improve several domains of social cognition, including emotion recognition and social perception. Among them, SCT provides non-pharmacological modality that particularly improve the domain of emotion recognition ( Yeo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, group leaders stressed the need to adhere to rules (showing respect, common curtesy) and for parental involvement or supervision when individuals decided to form their own online social groups ( 71 ). As tele-therapy and other on-line social and behavioral health interventions continue to expand, ( 72 , 73 ) (REF), future research needs to specify the advantages and disadvantages of these interventions for specific disability groups ( 74 ) (REF).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive dysfunctions account for most of the functional impairment of patients, are poorly responsive to antipsychotic treatments, thus still represent an unmet therapeutic need ( 5 , 16 , 26 , 27 , 192 194 ). Different reviews and metanalyses reported that cognitive remediation therapy, skills-based training and physical exercise, represent good treatment strategies that might be used as part of an integrated treatment to improve cognitive impairment of subjects with schizophrenia ( 56 60 , 69 , 195 199 ). Other psychosocial interventions, such as cognitive behavioral therapy and psychoeducation, which have been shown to improve psychosocial functioning, caregiver's burden and measures related to overall wellbeing (psychoeducation), could be effective in improving cognitive dysfunctions, but more research is needed to properly assess their effectiveness on this domain of functioning ( 51 54 , 192 , 200 203 ).…”
Section: Cognitive Dysfunctionsmentioning
confidence: 99%
“…It is an intervention of proven effectiveness to improve social skills in subjects with schizophrenia ( 38 , 40 , 45 ). It has an impact also on cognitive deficits, negative symptoms and psychosocial functioning ( 29 , 64 , 66 , 68 , 69 ) and has proved effective when associated with cognitive remediation or supported employment ( 45 ).…”
Section: Introductionmentioning
confidence: 99%